Hand Soap Based on Moringa Leaf to Reinforce Agro-Eco-Edu-Tourism in Generating Creative Younger Generation - Sugiyanto, Wardani; Yulvianah; Rosita, Risa; Darwati, Aan (SEAMEO BIOTROP, 2023)
Teaching Factory is a learning model that can be adopted in the Agro-Eco-Edu-Tourism (AEET) program. The learning model products in Teaching Factory are soap and hand sanitizer. The study's results reported that hand washing soap with the addition of Moringa leaf extract could inhibit the growth of Staphylococcus aureus and Escherichia coli bacteria that cause diarrheal disease. Diarrheal disease is still a public health problem in developing countries such as Indonesia because of its high morbidity and mortality. Diarrhea occurs due to the spreading S. aureus and E. coli bacteria, most often transmitted from hand to hand. Washing hands using soap and hand sanitizer is an activity that aims to remove dirt on hands.